The Effectiveness of Pregnancy Exercises on Back Pain among Third Trimester Pregnant Women - Novi Andani; Nila Widya Keswara (KHD Production, 2026)
Back pain is one of the most common discomforts experienced by pregnant women in the third trimester. Back pain can occur due to pressure on the back muscles or shifting of the spine, which puts pressure on joints. Back pain in pregnant women often arises from pressure on the back muscles or spinal shifts, leading to joint compression. This study aimed to evaluate the effectiveness of prenatal exercise in alleviating back pain among third-trimester pregnant women. A quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest, was employed. The population included all third-trimester pregnant women visiting PMB Safara Kedawung Kulon, totaling 35 individuals, who were sampled using a total sampling technique. Pain assessment was conducted using the standardized Face Pain Scale-Revised questionnaire, which did not require additional validity testing. Data were analyzed univariately through frequency percentages and bivariately using the Wilcoxon Signed Ranks Test. The results indicated that all respondents experienced back pain. During the pretest, the highest level of reported pain was more severe, experienced by 13 respondents (37.1%). Following the prenatal exercise intervention, the posttest showed that 18 respondents (51.4%) reported mild pain. Wilcoxon statistical testing yielded an Asymp. Sig. 0.001, demonstrating a significant difference between pretest and posttest results. Consequently, it was concluded that prenatal exercise has a significant effect on back pain in pregnant women in the third trimester. These findings advocate for the systematic integration of evidence-based exercise protocols into standard maternal healthcare practices, empowering midwives to offer safe, cost-effective pain management strategies that enhance maternal comfort and well-being during late pregnancy.